2021
DOI: 10.1021/acsaem.1c03282
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Activation of Amorphous NiFeMo Oxide Cocatalyst To Improve the Photoelectrochemical Water Splitting Performance of BiVO4

Abstract: Amorphous NiFeMo oxides (a-NiFeMo) synthesized via a simple supersaturated coprecipitation method are explored as a cocatalyst to improve the photoelectrochemical water splitting performance of BiVO 4 . The performance of the composite photoelectrode is found to be further enhanced through a cyclic-voltammetry-related in situ activation process, and a photocurrent of 5.0 mA/cm 2 is achieved at 1.23 V RHE with improved photoelectrochemical stability. X-ray photoelectron spectroscopy (XPS), Raman, and electron s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Bismuth vanadate, BiVO 4 , is a promising semiconductor oxide employed in photoanodes for the oxygen evolution reaction in water-splitting devices. , Its stability in contact with aqueous electrolytes, , its good visible light-harvesting capability, and its simple preparation through cheap wet techniques point to this material as a possible component of future commercial photoelectrochemical (PEC) cells. Furthermore, in the last 15 years the efficiency of BiVO 4 -based photoanodes (in terms of current density) rapidly grew from a few microamps per square centimeter in early reports to 4–5 mA cm –2 , with prolonged continuous operation of photoelectrodes modified with oxygen evolution cocatalysts. ,, However, the fast charge recombination of BiVO 4 -based electrodes still hampers the efficiency of this material. , …”
mentioning
confidence: 99%
“…Bismuth vanadate, BiVO 4 , is a promising semiconductor oxide employed in photoanodes for the oxygen evolution reaction in water-splitting devices. , Its stability in contact with aqueous electrolytes, , its good visible light-harvesting capability, and its simple preparation through cheap wet techniques point to this material as a possible component of future commercial photoelectrochemical (PEC) cells. Furthermore, in the last 15 years the efficiency of BiVO 4 -based photoanodes (in terms of current density) rapidly grew from a few microamps per square centimeter in early reports to 4–5 mA cm –2 , with prolonged continuous operation of photoelectrodes modified with oxygen evolution cocatalysts. ,, However, the fast charge recombination of BiVO 4 -based electrodes still hampers the efficiency of this material. , …”
mentioning
confidence: 99%
“…The photocurrent density of pristine BiVO 4 could be improved by up to 5.0 mA cm −2 at 1.23 V vs. RHE with an excellent long-term PEC stability. 80 In addition, Wang and co-workers demonstrated that the self-transformation of a precursor metal–organic framework could produce an oxygen defect enriched ultrathin Co(O)OH catalyst for improving the PEC performances of BiVO 4 photoanodes. As shown in Fig.…”
Section: The Structure Optimization Of Oer Catalysts In Pec Water Oxi...mentioning
confidence: 99%
“…The two vibrational peaks positioned at 344 and 937 cm −1 are corresponding to the bending mode and stretching mode of Mo−O in molybdate oxides, respectively, and a vibrational peak associated with NiFe−O was observed at 559 cm −1 . 27,29 Compared with the Raman characterization result of a-NiFeMo, 19,27 a-NiCoFeMo-0.03 had two additional vibrational peaks at 882.2 and 812.3 cm −1 , which may be attributed to the change in the coordination environment of Mo−O induced by the incorporation of Co. 30,31 Energy dispersive X-ray spectroscopy (EDX) revealed that Ni, Co, Fe, Mo, and O elements were uniformly distributed in a-NiCoFeMo-0.03, and no clear phase separation or element segregation can be observed (Figures 2c and S6). The results of XRD, Raman, and EDX indicate that amorphous nickel−cobalt−iron-blended molybdate oxides (a-NiCoFeMo) were successfully prepared by the supersaturated coprecipitation method when a low content of Co is incorporated.…”
Section: Morphology Structure and Composition Characterization Of The...mentioning
confidence: 99%
“…On the other hand, surface modification with transition metal (Ni, Co, Fe)-based oxygen evolution cocatalysts can reduce the water oxidation barrier of BiVO 4 , , thereby improving the interface-related water oxidation kinetics. Actually, not only limited to BiVO 4 , a similar cocatalyst modification strategy was also demonstrated to effectively improve the PEC performance of other kinds of photoelectrodes, such as α-Fe 2 O 3 and CuInS 2 , which further suggests that rational designing of a cocatalyst with functional properties is critical for achieving highly efficient photoelectrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation